A Bayesian learning model to predict the risk for cannabis use disorder. (1st July 2022) - Rajapaksha, Rajapaksha Mudalige Dhanushka S.; Filbey, Francesca; Biswas, Swati; Choudhary, Pankaj
Abstract: Background: The prevalence of cannabis use disorder (CUD) has been increasing recently and is expected to increase further due to the rising trend of cannabis legalization. To help stem this public health concern, a model is needed that predicts for an adolescent or young adult cannabis user their personalized risk of developing CUD in adulthood. However, there exists no such model that is built using nationally representative longitudinal data. Methods: We use a novel Bayesian learning approach and data from Add Health (n = 8712), a nationally representative longitudinal study, to build logistic regression models using four different regularization priors: lasso, ridge, horseshoe, and t. The models are compared by their prediction performance on unseen data via 5-fold-cross-validation (CV). We assess model discrimination using the area under the curve (AUC) and calibration by comparing the expected (E) and observed (O) number of CUD cases. We also externally validate the final model on independent test data from Add Health (n = 570). Results: Our final model is based on lasso prior and has seven predictors: biological sex; scores on personality traits of neuroticism, openness, and conscientiousness; and measures of adverse childhood experiences, delinquency, and peer cannabis use. It has good discrimination and calibration performance as reflected by its respective AUC and E/O of 0.69 and 0.95 based on 5-fold CV and 0.71 and 1.10 on validation data. Conclusion: This externally validated model may help in identifying adolescent or young adult cannabis users at high risk of developing CUD in adulthood. Highlights: Cannabis use disorder (CUD) is a serious public health issue in the US. Models are built to predict the future risk of CUD for adolescents/young adults. A nationally representative and longitudinal sample is used. The final model is externally validated on independent data. The model may help in identifying cannabis users at high risk of developing CUD.